Original paperEvaluation of knowledge about acne vulgaris among a selected population of adolescents of Tricity schools - Tałasiewicz, Konrad; Ołdakowska, Agnieszka; Szczerkowska-Dobosz, Aneta (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2012)
Introduction : It is estimated that approximately 80% of adolescents have different forms of acne vulgaris. Due to the high prevalence of the disease and its psycho-emotional impact on the quality of life, it is important to prevent the spread of misconceptions. Aim: To analyze the basic knowledge and misconceptions concerning acne vulgaris among adolescents. Material and methods: The study included 900 adolescents aged 15-19 years (mean age: 17.47 years), 401 females, 493 males attending high schools (n = 481) or technical colleges (n = 419). The study was based on a direct anonymous questionnaire that consisted of fourteen multiple choice questions. Results: On average, 50.3% of questions were answered correctly. 57.8% of participants stated that they had suffered from acne. As regards the causes, more than half (59.5%) of participants stated that acne is connected to eating and hygiene habits. 40.5% of students considered acne infectious. The study revealed that many “false beliefs” exist. 26.4% of adolescents believe that starting sexual activity can influence healing. Considering the effectiveness of curing acne in adolescence, 24.2% of participants do not see a point in early treatment. Regarding the sources of knowledge about acne, most adolescents use the internet, teenage newspapers and friends' opinions. Only 41.2% want to learn more, and almost 90% consider their knowledge sufficient. Conclusions : The results from a large population-based study indicate that the knowledge about acne is insufficient, which reveals the need for introducing educational programs in schools.